2002
DOI: 10.1016/s0006-3495(02)75203-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Proteins in Crystals: Comparison of Experiment with Simple Models

Abstract: The dynamic behavior of proteins in crystals is examined by comparing theory and experiments. The Gaussian network model (GNM) and a simplified version of the crystallographic translation libration screw (TLS) model are used to calculate mean square fluctuations of C(alpha) atoms for a set of 113 proteins whose structures have been determined by x-ray crystallography. Correlation coefficients between the theoretical estimations and experiment are calculated and compared. The GNM method gives better correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
286
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(308 citation statements)
references
References 22 publications
21
286
1
Order By: Relevance
“…3-5, 16, 24, 37 It was shown that the GNM is about one order more efficient than most other approaches. 48 Improvements to these approaches have been developed for many aspects, including crystal periodicity and cofactor corrections, 17,21,22,35 and density -cluster rotational -translational blocking. 11 These approaches have been applied to the study of large proteins or protein complexes, such as, hemoglobin, 47 F1 ATPase, 10,50 chaperonin GroEL, 20, 49 viral capsids, 29,36 and ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…3-5, 16, 24, 37 It was shown that the GNM is about one order more efficient than most other approaches. 48 Improvements to these approaches have been developed for many aspects, including crystal periodicity and cofactor corrections, 17,21,22,35 and density -cluster rotational -translational blocking. 11 These approaches have been applied to the study of large proteins or protein complexes, such as, hemoglobin, 47 F1 ATPase, 10,50 chaperonin GroEL, 20, 49 viral capsids, 29,36 and ribosome.…”
Section: Introductionmentioning
confidence: 99%
“…Such lowenergy eigenvalues reflect the long-time behavior of the protein dynamics beyond the reach of MD simulations. 6,8,36,55,58 These approaches have been improved in many aspects including crystal periodicity corrections 28,34,35,54 and densitycluster rotational-translational blocking. 20 These methods are relatively inexpensive particularly in their coarse-grained settings.…”
Section: Introductionmentioning
confidence: 99%
“…3A) gave a coefficient of 0.71. For comparison, this value is at the upper end of correlation coefficients calculated for crystal structures by using other theoretical methods such as Gaussian network models (29). The improvement in correlation seems to result primarily from averaging of stochastic variations within the mobile, extracellular regions of OmpA.…”
Section: Resultsmentioning
confidence: 99%